1971
DOI: 10.1073/pnas.68.7.1653
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Action of Vitamin K: Evidence for the Conversion of a Precursor Protein to Prothrombin in the Rat

Abstract: Previous studies have shown that the vitamin K-induced synthesis of prothrombin in a vitamin K-deficient rat is only slightly inhibited by cycloheximide treatment. Rat prothrombin has now been purified by disc electrophoresis after BaSO4 adsorption and citrate elution. When cycloheximide (5 mg/kg) was given to vitamin K-deficient rats 30 min before vitamin K, about 70% of the amount of prothrombin seen in rats not treated with cycloheximide was produced (two-stage assay), and the prothrombin band could be seen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
1

Year Published

1976
1976
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(23 citation statements)
references
References 27 publications
1
21
1
Order By: Relevance
“…These hypotheses include regulation at the levels of transcription (3), translation (4)(5)(6), and, more recently, at the post-translational level (7)(8)(9)(10). During the past several years, much attention has been focused on the possibility that the inactive "abnormal" prothrombins (11)(12)(13) present in animals deficient in vitamin K or receiving coumarin anticoagulants may represent an unmodified species of mature prothrombin, i.e., precursor prothrombin.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…These hypotheses include regulation at the levels of transcription (3), translation (4)(5)(6), and, more recently, at the post-translational level (7)(8)(9)(10). During the past several years, much attention has been focused on the possibility that the inactive "abnormal" prothrombins (11)(12)(13) present in animals deficient in vitamin K or receiving coumarin anticoagulants may represent an unmodified species of mature prothrombin, i.e., precursor prothrombin.…”
mentioning
confidence: 99%
“…Because preliminary studies with Nonidet P-40 indicated that this detergent inhibited the clotting activity associated with the assay of Shapiro and Waugh (24) (but not that of the Echis carinatus assay), the prothrombin contained in 105,000 X g supernatant fractions was initially adsorbed to barium sulfate (7,25) prior to assessing clotting activity. Adsorption was conducted as previously described (7,25) barium treatment (see Tables 1 and 2). Thus, the ability to discriminate between preprothrombin and prothrombin in various cell and medium fractions was based not only on two distinct clotting assays, but also on the well-established ability of prothrombin to be selectively adsorbed to insoluble barium salts.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, VKD-␥-carboxylases change glutamic acid residues in blood clotting factors into ␥-carboxylated glutamic acid (35). VKD-␥-carboxylase requires epoxidation of vitamin K for this modification (36). The SdpB homology to VKD-␥-carboxylases is restricted mostly to the N-terminal portion of VKD-␥-carboxylases specifically from amino acids 13 to 283 (34).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the protein was electrophoretically distinguishable from normal prothrombin [11]. Very soon thereafter, in another insightful experiment, Shah and Suttie [13] injected vitamin K-deficient rats with radioactive amino acids and showed that the action of vitamin K was to convert an inactive precursor version of prothrombin to an active one. …”
Section: The Vitamin K Storymentioning
confidence: 99%